AB0073 The s100a9 inhibitor paquinimod (abr-215757) ameliorates experimental osteoarthritis with high synovial involvement. (23rd January 2014) - Schelbergen, R.; Blom, A.; Leanderson, T.; Eriksson, H.; van den Berg, W.; van Lent, P.
Abstract : Background: There is increasing evidence that synovial activation contributes to osteoarthritis (OA) pathology and that it is present in a large subset of OA patients. Previously, we found that alarmins S100A8 and S100A9 are elevated in the synovium of OA patients and that high S100A8/A9 serum levels correlate with 2-year progression of the disease. Furthermore, these S100-proteins are involved in cartilage degradation and synovial activation in experimental OA. Paquinimod is a quinoline-3-carboxamide compound with immunomodulatory properties that is currently in clinical development for treatment of systemic sclerosis. It targets the S100A9 protein and disrupts the binding of S100A9 to RAGE and TLR-4. Objectives: In the current study we investigated the effect of the S100A9-blocking compound paquinimod on experimental osteoarthritis with different degrees of synovial involvement. Methods: Collagenase induced OA (CIOA) was induced by two times intra-articular injection of 1U collagenase and DMM was induced by transsection of the medial anterior meniscotibial ligament leading to destabilization of the medial meniscus (DMM), both in C57Bl6 mice. CIOA measurements were done at day 42, DMM at day 56. Paquinimod (71, 5 μM) was administered in the drinking water 4 days before induction of OA in both CIOA and DMM and refreshed twice a week. Synovial thickening and cellularity was measured using an arbitrary score from 0-3. OA-like cartilage pathology was scored using a modified Pritzker OARSI score. Osteophyte size was assessed by a blinded observer using imaging software. Results: We assessed the effect of paquinimod-treatment on two different experimental OA models. In CIOA, synovial activation is high throughout day 42 of the model, whereas during DMM synovial activation is marginal. We started with paquinimod-treatment of DMM mice and focused first on osteophytes. These are bony outgrowths that limit joint formation, originating from the periosteum or from ligaments. No differences were observed on osteophyte size between paquinimod-treated and non-treated animals at both medial tibia and medial femur. Furthermore, OA-like cartilage pathology was only significantly reduced by paquinimod-treatment at the medial femur (64%), not at other surfaces and not in the total joint score (16%). Next, we investigated the effect of paquinimod-treatment in an OA model with synovial activation. In CIOA, synovial activation was significantly reduced by paquinimod-treatment at the medial side of the patella-femur region (57%). Osteophyte size was significantly reduced at the medial femur (66%) and cruciate ligaments (67%). Finally, OA-like cartilage pathology was significantly reduced in CIOA after paquinimod treatment on the medial side of both tibia and femur (47% and 75% respectively) as well as in the total joint score (46%). Conclusions: Blocking S100A9 with paquinimod reduces synovial activation, osteophyte formation and OA-like cartilage pathology in CIOA. In contrast, in an experimental OA model where synovial activation is nearly absent (DMM), the effect of paquinimod is marginal. Paquinimod could prove a very promising treatment for osteoarthritis patients with high synovial activation by blocking S100A9. Disclosure of Interest: None Declared